Prognostic Value of 18F-FDG PET/CT Metabolic Parameters in Surgically Treated Stage I Lung Adenocarcinoma Patients. (August 2021) - Tosi, Davide; Pieropan, Sara; Cattoni, Maria; Bonitta, Gianluca; Franzi, Sara; Mendogni, Paolo; Imperatori, Andrea; Rotolo, Nicola; Castellani, Massimo; Cuzzocrea, Marco; Schiorlin, Ilaria; Casagrande, Sabrina; et al.
Abstract : Purpose of the Report: This article aims to explore the prognostic role of 18 F-FDG PET/CT metabolic parameters in stage I lung adenocarcinoma patients. Patients and Methods: One hundred eighty pathological stage I lung adenocarcinoma patients were retrospectively reviewed. Semiquantitative analysis of FDG tumor uptake was performed with TrueD software on the Siemens Leonardo workstation. SUVmean and MTV were calculated using SUV threshold of 41% of SUVmax ; the total lesion glycolysis (TLG) was calculated as the product of SUVmean and MTV. Correlation was evaluated using Spearman correlation coefficient. Maximally selected rank statistics was performed to detect the optimal cutoff used for dichotomizing each PET parameter (6.5 for SUVmean, 9.6 for SUVmax, and 19.1 for TLG). Results: Our main finding was the significant correlation between 18 F-FDG PET/CT parameters (SUVmean, SUVmax, and TLG) and disease-free survival in pathologic stage I non–small cell lung cancer. SUVmean has the greatest accuracy in recurrence prediction (integrated area under the curve, 0.803; 95% confidence interval, 0.689–0.918). We run the maximally selected rank statistics to provide the classification of observations in 2 groups by a continuous predictor parameter; the free from recurrence rate was significantly greater in patients with SUVmean ⩽6.5, SUVmax ⩽9.6, and TLG ⩽19.1. Conclusions: Our research supports the hypothesis that SUVmean, SUVmax, and TLG are well correlated with free from recurrence rate in stage I adenocarcinoma patients, subjected to pulmonary lobectomy. Our findings also indicate these markers as promising prognostic indicators.